Diastereoselective synthesis of 1,1,4-trisubstituted-2,3,4,9-tetrahydrospiro-beta-carbolines via glacial acetic acid catalyzed pictet - spengler reaction - Shumaila, Abdullah M. A.; Puranik, Vedavati G.; Kusurkar, Radhika S. (Arkivoc, 2011)
The Pictet-Spengler reaction of substituted tryptamines with cyclic ketones using glacial acetic acid afforded only one diastereomer of unreported 1,1,4-trisubstituted-2,3,4,9-tetrahydrospiro-beta-carbolines. The stereoselectivity in the reaction has been demonstrated using unsymmetrical ketones and single-crystal X-ray analysis of one of the spiro products in the form of base, its sulfate and hydrochloride salts, which indicated the formation of only the R, R diastereomer.
Keywords: 1; 3; 4; 4-Trisubstituted-2; 9-tetrahydrospiro-beta-carbolines; beta-substituted tryptamine; Diastereoselective Pictet-Spengler reaction; Glacial acetic acid